More precious than peace : a new history of America in World War I - Doenecke, Justus D. (University of Notre Dame Press, 2022)
Justus D. Doenecke's monumental study covers diplomatic, military, and ideological aspects of U.S. involvement as a full-scale participant in World War I.The entry of America into the "war to end all wars" in April 1917 marks one of the major turning points in the nation's history. In the span of just nineteen months, the United States sent nearly two million troops overseas, established a robust propaganda apparatus, and created an unparalleled war machine that played a major role in securing Allied victory in the fall of 1918. At the helm of the nation, Woodrow Wilson and his administration battled against political dissidence, domestic and international controversies, and their own lack of experience leading a massive war effort.In More Precious than Peace, the long-awaited successor to his critically acclaimed work Nothing Less than War, Justus D. Doenecke examines the entirety of the American experience as a full-scale belligerent in World War I. This book covers American combat on the western front, the conscription controversy, and scandals in military training and production. Doenecke explores the Wilson administration's quest for national unity, the Creel Committee, and'patriotic'crusades. Weaving together these topics and many others, including the U.S. reaction to the Russian revolutions, Doenecke creates a lively and comprehensive narrative. Based on impressive research, this balanced appraisal challenges historiographical controversies and will be of great use to students, scholars, and any reader interested in the history of World War I.